A Technical Feasibility of Aqueous Aerosol Generation Based on the Flashing Jet: Effects of Overheat Degree, Jetting Rate, Jetting Volume, and Liquid Type - Qi-Wen Zheng; Li-Jia Yuan; Jian Wang (Georg Thieme Verlag KG, 2023)
A previously established flashing jet inhaler prototype (FJ prototype) can produce an aqueous aerosol but cannot steadily provide inhalable aerosol (2-5 μm). This study aims to optimize the atomization performance of the FJ prototype and generate inhalable aqueous aerosols. The effects of overheat degree, jetting rate, jetting volume, and liquid type on atomization performance were assessed by determining output aerosol's mass median aerodynamic diameter (MMAD) and aerodynamic particle size distribution. Drug distribution of active ingredients in different liquid types was also measured. A Pari nebulizer was used as a reference device. Our data suggested that MMAD is negatively correlated with the overheat degree and jetting rate, but has no significant relationship with the jetting volume. The effect of jetting rate is weaker than that of the overheat degree. When normal saline was used as the atomization liquid, output aerosol's MMAD at the FJ prototype and Pari nebulizer were 1.98 ± 0.18 and 2.50 ± 0.81 μm, respectively. The addition of a surfactant significantly decreases MMAD both in solution and in suspension, but the suspended particles had no effect on the residual level and atomization performance of the FJ prototype. When ventolin was used as the atomization liquid, the MMAD of the FJ prototype and Pari nebulizer was 2.1 ± 0.2 and 1.7 ± 0.2 μm, respectively, while the fine particle dosage (FPD) in percent of the nominal dose (%ND) was 50.4 ± 3.1 and 53.1 ± 7.2%, respectively. When pulmicort respules was used as the atomization liquid, the MMAD of the FJ prototype and Pari nebulizer was 2.5 ± 0.5 and 4.6 ± 0.2 μm respectively, while the FPD (%ND) was 30.1 ± 5.6 and 58.6 ± 5.1%, respectively. The FJ prototype not only delivers inhalable aqueous aerosol but also has a potential advantage in the atomization of suspension or poorly soluble drugs.